Does Intellectual Capital Influence Sustainability Reporting in Indonesia’s Energy and Mining Industry? Moderating Role of Audit Committee - Suwarno Suwarno; Syaiful Syaiful (Journal of Enterprise and Development (JED), 2025)
Purpose: This study aims to investigate the influence of intellectual capital on sustainability reporting within the energy and mining industry in Indonesia. Additionally, it examines whether this influence is moderated by audit committee.Method: This research employs a quantitative approach, utilizing secondary data from 32 energy and mining companies listed on the Indonesia Stock Exchange (IDX) for the period of 2020–2023. Partial least squares structural equation modeling (PLS-SEM) was applied to test the hypotheses.Result: The findings reveal several significant outcomes. First, intellectual capital positively influences sustainability reporting. Second, audit committee serves as a moderator in the relationship between intellectual capital and sustainability reporting.Practical Implications for Economic Growth and Development: This study underscores the necessity for firms to enhance their internal capabilities, particularly in the domains of intellectual capital and governance functions, to improve sustainability disclosures. Such improvements may promote transparency, bolster investor confidence, and contribute to sustainable economic development in emerging markets.Originality/Value: This research contributes to the resource-based view theory and agency theory by illustrating the dual role of governance mechanisms in sustainability practices and providing new evidence regarding the contingent relationship between intellectual capital and sustainability reporting within the context of a developing country.